2013
DOI: 10.1007/s00340-013-5463-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of volatile coatings on the laser-induced incandescence of soot

Abstract: We have measured time-resolved laser-induced incandescence (LII) from combustion-generated mature soot extracted from a burner and (1) coated with oleic acid or (2) coated with oleic acid and then thermally denuded using a thermodenuder. The soot samples were size selected using a differential mobility analyzer and characterized with a scanning mobility particle sizer, centrifugal particle mass analyzer, and transmission electron microscope. The results demonstrate a strong influence of coatings on the magnitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 97 publications
4
48
0
Order By: Relevance
“…When the remaining oleic acid is removed in the thermodenuder, the measured particle sizes shrink to the size distribution of the core soot particles. This effect is more pronounced for heavily coated particles, which is consistent with recent results based on laser-induced incandescence studies [75].…”
Section: Effects Of Laser Heating On Particle Morphologysupporting
confidence: 82%
See 4 more Smart Citations
“…When the remaining oleic acid is removed in the thermodenuder, the measured particle sizes shrink to the size distribution of the core soot particles. This effect is more pronounced for heavily coated particles, which is consistent with recent results based on laser-induced incandescence studies [75].…”
Section: Effects Of Laser Heating On Particle Morphologysupporting
confidence: 82%
“…More compact aggregates have a smaller effective surface area. Our results [112] have shown that the LII signal decay rate can be substantially reduced for aggregates with larger fractal dimensions. Coating and denuding the particles causes the aggregates to become more compact, increasing the fractal dimension from an average of 1.88 for the uncoated particles (Fig.…”
Section: Effects Of Morphology On the LII Signalmentioning
confidence: 50%
See 3 more Smart Citations